Flexural behaviour of reinforced concrete with rectangular hollow section - Muhammad Nur Alif, Azman (2013)
Beam is a structural member which spans horizontally between supports, made of steel, reinforced concrete, wood or composite. In Malaysia, reinforced concrete beam is the preferred choice as structure. However, the self-weight of reinforcement beam quite significant to the overall dead load in the structure which transferred to the foundation. Thus, the idea of providing hollow section to the beam was to reduce the weight of the beam as overall structure weight structure was generally. The concept introduced was the same as hollow slab panels which been widely used in bridge and highway construction where this will reduce the cost and material wastage at the same time. Referring to the second moment of inertia law, the reduction of the surface area of the beam due to the hollow will give an effect on the bending moment and shear resistance of the beam. Therefore, an experimental testing was necessary in order to identify the reduction of beam sample strength, deflection profile and the crack pattern. Four sample of beam with hollow size varies from 20 mm to 110 mm were prepared as well as a solid beam as a control and tested with four point flexural test to determine the flexural strength, deflection and crack pattern. Three LVDT were placed under the beam to measure the deflection and the cracks were marked to indicate the propagation and type of crack. From the results, each of the specimens was test with the four point test. The result shows that the flexural strength of the concrete beam depends on the surface area. Result shows, flexural strength decreases when the size of the rectangular hollow were increasing. Rectangular hollow of the beam make the total surface area decreases. It also decreased the second moment of inertia at the beam. Beam tend to fail and produce crack pattern in small load because the decreased of the second moment inertia.